THE DEVELOPMENT OF ISLAMIC ECONOMICS IN VARIOUS PARTS OF THE WORLD - MEIRISON MEIRISON (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". In the Famous Hotel in heart of London, England, is full of bankers, lawyers, and top world investors. Those who come from various countries in Asia, Europe, and the Middle East, make mutual offers, and many end up on signing the deal. One country absent on this event: USA. Islamic finance - which became increasingly global after Britain adopted it - has grown tremendously over the past decade. This economic system has attracted all key international players, leaving the United States in the increasingly profitable global industry. According to the report, 2016 saw new trends across the various sectors of the Islamic economy. In the halal food sector, which saw Muslim spending reach 4 trillion dirhams ($ 1.1 trillion) in 2014, new partnerships have been forged between countries such as the UAE, South Korea, Malaysia, Indonesia and South Africa. Sukuk listings in Malaysia and the UAE have also contributed to the growth of the Islamic finance sector, which grew to 6.6 trillion dirhams ($ 1.8 trillion) in 2014, helped by regional initiatives such as the UAE-Bahrain partnership and Avriland First launched the first Islamic window in Cameroon.